AN ANALYSIS OF STUDENTS’ READING SKILLS BY USING MIND MAPPING TECHNIQUE - Ivan Asep Supriadi; elva utami; Melati Melati (Edu-Ling: Journal of English Education and Linguistics, 2020)
Although reading has been learned by students since they start to learn the English language but it still becomes the most difficult skill to be acquired than speaking, writing, and listening. It is a possibility caused by the students have a limitation of knowledge about reading roles, different learning styles, lazy to read, and low motivation for effective reading because of a too-long passage and different types of text. Therefore, students must be serious to acquire this skill. In this article, the writers would like to introduce a suitable approach for teaching reading using mind mapping techniques. The results of the data, the researcher concludes that the students’ have some difficulties in identifying reading skills and understanding the mind mapping, many of the students have difficulties in this factor because the result shows a high number of percentage give the answer very not good and not good. The last is the result of learning English, most of the students have enough understood about teaching and learning English. After reading this article, the writer expects that this article can help English teachers to apply suitable approach for teaching reading of English texts.